2007
DOI: 10.1002/syn.20467
|View full text |Cite
|
Sign up to set email alerts
|

Continuous nicotine administration produces selective, age‐dependent structural alteration of pyramidal neurons from prelimbic cortex

Abstract: Emerging evidence indicates that adolescence represents a developmental window of enhanced nicotine-induced neuroplasticity in rat forebrain. However, whether nicotine produces age-dependent structural alteration of neurons from medial prefrontal cortex remains to be determined. We characterized the dendritic morphology of layer V pyramidal neurons from prelimbic cortex following adolescent (P29-43) or adult (P80-94) nicotine pretreatment. Nicotine administration was via osmotic pump [initial dose 2.0 mg/(kg d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 45 publications
3
63
1
Order By: Relevance
“…Nicotine's effects on nicotinic acetylcholine receptors and regional blood flow in the brain are complex, important, and incompletely understood. Chronic exposure is known to change the structural plasticity of the brain [36,37]. Nicotinic receptor activation acutely causes the release of dopamine, glutamate, norepinephrine, acetylcholine, serotonin, B-endorphin, and gamma-aminobutyric acid (GABA), and acute smoking cessation causes a state of ''subnormal release of dopamine and other neurotransmitters [38].''…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine's effects on nicotinic acetylcholine receptors and regional blood flow in the brain are complex, important, and incompletely understood. Chronic exposure is known to change the structural plasticity of the brain [36,37]. Nicotinic receptor activation acutely causes the release of dopamine, glutamate, norepinephrine, acetylcholine, serotonin, B-endorphin, and gamma-aminobutyric acid (GABA), and acute smoking cessation causes a state of ''subnormal release of dopamine and other neurotransmitters [38].''…”
Section: Discussionmentioning
confidence: 99%
“…Results revealed that adolescent nicotine resulted in increased branching complexity of basilar dendrites of neurons with complex apical tufts, while adult dosing induced increasing branching only in those with simple tufts. Thus, we concluded that both adolescent and adult nicotine induce growth of dendrites in mPFC neurons, but the effects are on different populations of neurons, with putatively different connectivity, at different ages (Bergstrom et al, 2008). Unlike the differences between MSNs and aspiny cell types, where MSNs are clearly part of the reinforcement system and aspiny neurons are not, classification of layer 5 pyramidal neurons by projection field or function is less clear.…”
Section: Adolescent Nicotine and Medial Prefrontal Cortex Dendritic Mmentioning
confidence: 96%
“…Moreover, it has been suggested that in addition to a different timing, there might be a different developmental mechanism between mPFC and Acb, as dopamine D1 and D2 receptors in the mPFC undergo overproduction, which subsequently leads to massive pruning during adolescence, whereas Acb dopamine receptors show overproduction at P40, but virtually no pruning occurs (Andersen et al, 2000). Also, adolescent nicotine exposure has long-term effects on morphology of a subpopulation of pyramidal neurons in the mPFC, seen as an increase in dendritic length of complex pyramidal cells (Bergstrom et al, 2008). These persistent changes induced by adolescent exposure to nicotine may be brought about by the increased induction of plasticity-associated genes, which were found to be specifically upregulated in the mPFC of animals treated with nicotine during adolescence (Schochet et al, 2005).…”
Section: Adolescent Nicotine Exposure and Dopamine Releasementioning
confidence: 99%